ANALISIS BIBLIOMETRIK TERKAIT PENELITIAN KREATIVITAS DAN PRODUKTIVITAS PUSTAKAWAN DALAM MENDUKUNG RISET DAN INOVASI - Tupan, Tupan (Jurnal Perpustakaan dan Informasi, 2024)
A bibliometric analysis of creativity and productivity of librarians in research institutions was conducted with the aim of determining the development of creativity and productivity research based on years, the development of creativity and productivity research based on keywords, the distribution of main journals in research on creativity and productivity of librarians, and cluster analysis of research networks on creativity and productivity of librarians. Data collection using keywords (TITLE-ABS-KEY ("Librarian creativity") OR TITLE-ABS-KEY ("Librarian productivity") OR TITLE-ABS-KEY ("Librarian support for research") OR TITLE-ABS-KEY ("Library innovation") OR TITLE-ABS-KEY ("Role of librarians in research") OR TITLE-ABS-KEY ("Research facilitation by librarians") OR TITLE-ABS-KEY ("Collaboration between librarians and researchers"). Inclusion data of 106 documents were processed using R-biblioshiny and VosViewer software. The results of the analysis show that the main journals that publish the development of librarian creativity and productivity research are Librar Management, followed by Library Philosophy and Practice, Libri, Public Library Quarterly, Library Review, Architectural Research Quarterly, Indian Journal of Information Sources and Services, Journal of Library Administration. Librarians in research institutions are expected to be able to innovate and support research more proactively as seen from the keyword analysis, namely library innovation, innovation, library services, library performance, library management, productivity, collaboration, digital library. Interventions in the form of creative training and skill enhancement such as digital library, collaboration, design thinking, intelligent infrastructure, visioning practice are very effective in improving the ability of librarians to support research and innovation. The results of the network cluster analysis show that the topics of big data, innovation capability, makerspaces, library innovation, library performance, personal training, service design, service innovation, design thinking, intelligent infrastructure, visioning practice are research topics conducted in 2018-2024.